Genetic mechanisms and correlational selection structure trait variation in a coral snake mimic. Issue 1947 (17th March 2021) - Curlis, John David; Davis Rabosky, Alison R.; Holmes, Iris A.; Renney, Timothy J.; Cox, Christian L.
Abstract : Covariation among traits shapes both phenotypic evolution and ecological interactions across space and time. However, rampant geographical variation in the strength and direction of such correlations can be particularly difficult to explain through generalized mechanisms. By integrating population genomics, surveys of natural history collections and spatially explicit analyses, we tested multiple drivers of trait correlations in a coral snake mimic that exhibits remarkable polymorphism in mimetic and non-mimetic colour traits. We found that although such traits co-occur extensively across space, correlations were best explained by a mixture of genetic architecture and correlational selection, rather than by any single mechanism. Our findings suggest that spatially complex trait distributions may be driven more by the simple interaction between multiple processes than by complex variation in one mechanism alone. These interactions are particularly important in mimicry systems, which frequently generate striking geographical variation and genetic correlations among colour pattern traits.